Legal Cannabis, and Then… - Bostancı Demirci, Hadiye; Acar, Sevda; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2020)
Recently, it is seen that the regulations regarding the use of psychoactive substances such as cannabis are considered just as a public security problem in specific periods and it is expected to be controlled by legal precautions. However, with the realization that the problem of substance use and addiction is not a mere public security problem, treatment and prevention activities have started to be given importance. In recent years, it has been observed that people who both regulate medical treatment, and work on the legal framework and related to the psychosocial dimension of the incident, have been working sensitively on legal regulations and new developments. From now on the substance use is evaluated within “public health and society safety”, and along with this, especially cannabis regulations are being changed rapidly and the issue is still being discussed in many countries. It is thought that it will be difficult to predict the long-term consequences of these practices as the basis of both individual and societal in terms of public health and public safety. This article is written in order to summarize the individual and social consequences that may arise if the use of recreational cannabis is allowed by compiling the studies regarding the subject.